Justifying the use of âUm-ol-Baabâ in Syntax - Ibrahim Mohammad Al-Bab (دراسات في اللغة العربيّة وآدابها)
This research is concerned with a concept called âUm-ol-Baabâ, which has wide applications in syntax. This article attempts to clarify this concept and specify terms which are used to directly or indirectly refer to it. This has been done by examining the views and works of a good number of syntacticians. Three subgroupings have been revealed :1) devices the structure of which are compatible with their meanings, 2) devices which are questionable as to their meaning or purpose , and 3) devices the structure of which does not match their meanings. Syntactic scholars suppose that these devices have unique properties. The investigation of the syntactic categories of some of the verbs yielded significant findings and revealed justifications for this term. Those justifications are sometimes related to forms, sometimes related to content, and sometimes to both.